Properties and Biotechnological Applications of Acyl‐CoA:diacylglycerol Acyltransferase and Phospholipid:diacylglycerol Acyltransferase from Terrestrial Plants and Microalgae. Issue 7 (25th September 2018) - Xu, Yang; Caldo, Kristian Mark P.; Pal‐Nath, Dipasmita; Ozga, Jocelyn; Lemieux, M. Joanne; Weselake, Randall J.; Chen, Guanqun
Abstract: Triacylglycerol (TAG) is the major storage lipid in most terrestrial plants and microalgae, and has great nutritional and industrial value. Since the demand for vegetable oil is consistently increasing, numerous studies have been focused on improving the TAG content and modifying the fatty‐acid compositions of plant seed oils. In addition, there is a strong research interest in establishing plant vegetative tissues and microalgae as platforms for lipid production. In higher plants and microalgae, TAG biosynthesis occurs via acyl‐CoA‐dependent or acyl‐CoA‐independent pathways. Diacylglycerol acyltransferase (DGAT) catalyzes the last and committed step in the acyl‐CoA‐dependent biosynthesis of TAG, which appears to represent a bottleneck in oil accumulation in some oilseed species. Membrane‐bound and soluble forms of DGAT have been identified with very different amino‐acid sequences and biochemical properties. Alternatively, TAG can be formed through acyl‐CoA‐independent pathways via the catalytic action of membrane‐bound phospholipid:diacylglycerol acyltransferase (PDAT). As the enzymes catalyzing the terminal steps of TAG formation, DGAT and PDAT play crucial roles in determining the flux of carbon into seed TAG and thus have been considered as the key targets for engineering oil production. Here, we summarize the most recent knowledge on DGAT and PDAT in higher plants and microalgae, with the emphasis on their physiological roles, structural features, and regulation. The development of various metabolic engineering strategies to enhance the TAG content and alter the fatty‐acid composition of TAG is also discussed.